Epicardial electroanatomical mapping, radiofrequency ablation, and lesion imaging in the porcine left ventricle under real-time magnetic resonance imaging guidance—an in vivo feasibility study. Issue Volume 20:Issue FI 2(2018) (26th December 2017) - Mukherjee, Rahul K; Roujol, Sébastien; Chubb, Henry; Harrison, James; Williams, Steven; Whitaker, John; O'Neill, Louisa; Silberbauer, John; Neji, Radhouene; Schneider, Rainer; Pohl, Thomas; Lloyd, Tom; et al.
Abstract: Aims: Magnetic resonance imaging (MRI) is the gold standard for defining myocardial substrate in 3D and can be used to guide ventricular tachycardia ablation. We describe the feasibility of using a prototype magnetic resonance-guided electrophysiology (MR-EP) system in a pre-clinical model to perform real-time MRI-guided epicardial mapping, ablation, and lesion imaging with active catheter tracking. Methods and results: Experiments were performed in vivo in pigs ( n = 6) using an MR-EP guidance system research prototype (Siemens Healthcare) with an irrigated ablation catheter (Vision-MR, Imricor) and a dedicated electrophysiology recording system (Advantage-MR, Imricor). Following epicardial access, local activation and voltage maps were acquired, and targeted radiofrequency (RF) ablation lesions were delivered. Ablation lesions were visualized in real time during RF delivery using MR-thermometry and dosimetry. Hyper-acute and acute assessment of ablation lesions was also performed using native T1 mapping and late-gadolinium enhancement (LGE), respectively. High-quality epicardial bipolar electrograms were recorded with a signal-to-noise ratio of greater than 10:1 for a signal of 1.5 mV. During epicardial ablation, localized temperature elevation could be visualized with a maximum temperature rise of 35 °C within 2 mm of the catheter tip relative to remote myocardium. Decreased native T1 times were observed (882 ± 107 ms) in the lesion core 3–5 min after lesion delivery and relative location of lesions matched well to LGE. There was a good correlation between ablation lesion site on the iCMR platform and autopsy. Conclusion: The MR-EP system was able to successfully acquire epicardial voltage and activation maps in swine, deliver, and visualize ablation lesions, demonstrating feasibility for intraprocedural guidance and real-time assessment of ablation injury.